Description of Beckman Glucose Analyzer - Sternberg, James C. (1969)
Description of the Beckman Glucose Analyzer written by Dr. James Sternberg. This draft was sent to another Beckman Instruments' employee for feedback, with the ultimate intention of using it in a magazine article and for other publicity purposes. This description may differ from the version that was ultimately published and used for marketing. The Glucose Analyzer was developed by James Sternberg in 1969 and was one of several very successful medical testing and analysis instruments that Beckman Instruments produced in the 1970s. Its size, speed, and price enabled doctors to get fast, in-house results, instead of sending patients’ blood samples to a lab and awaiting a report.
Keywords: Glucose--Analysis; Blood sugar; Scientific apparatus and instruments; Beckman Instruments, Inc.